Analisis Penerjemahan dan Makna Secara Tepat Lirik Lagu “I Think They Call This Love” By Elliot James Ray - Abrar Ramadhanu Bustami (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the denotative, connotative, and moral meanings contained in the lyrics of the song "I Think They Call It Love" by Eliot James Ray. This song was chosen because it represents the universal emotion and complexity of falling in love, yet presented with poetic diction. The research method used was descriptive qualitative with a Roland Barthes-style semiotic approach, which focuses on the analysis of levels of signs (denotation, connotation, and myth/ideology). The results show that the song’s lyrics go beyond the usual depiction of romantic love. Denotatively, the lyrics describe doubt and the process of recognizing new feelings. Connotatively, they contain symbolism regarding the emotional struggle, vulnerability, and enlightenment that accompany the realization of love. The ultimate conclusion is that this song defines love not only as an emotion but also as a process of self-acceptance and the courage to feel. The semiotic analysis successfully elucidates the moral message about the importance of emotional honesty and the essential meaning of a relationship.